Get out of that pit : straight talk about God's deliverance from a former pit-dweller - Moore, Beth, 1957-; Moore, Beth (Nashville, TN : Integrity Publishers, 2007)
"Helpful lessons for those who feel like they live in a state of confusion"--Provided by publisher.
Includes bibliographical references (p. 211-212).
Keywords: Christian life